The Metaphor of "Center" in Planning: Learning from the Geopolitical Order of Swidden Traditions in the Land of Sunda - Setiadi, Hafid; Yunus, Hadi Sabari; Purwanto, Bambang (Journal of Regional and City Planning, 2017)
Abstract. This study intends to open a new discourse about the role and position of the center in the field of regional and urban planning by using it as a metaphor. By using a metaphoric deconstruction method, the study examines the changes in geopolitical order and in the concept of the center in the Land of Sunda, which based on the swidden tradition as an implication of Hindu and Islamic influences. The study shows that from before the arrival of Hinduism until the height of Islamic power in the 15th century, the geopolitical order in the Land of Sunda has transformed from (1) an egalitarian system without center to (2) anÂ  egalitarian system with a hidden center and then to (3) aÂ  hierarchical-network system with noticeable and bold center. However, the swidden tradition remains, which is mainly evident from the use of the concepts of âinsideâ and âoutsideâ for representing the principles of autonomy and alliance respectively.Â  The two principles have been the main features of the geopolitical order in the Land of Sunda with its ecological and pluralistic nature.Â  These principles teach that the center is not always identified as a dominant and absolute power. The center is not the only decisive point that determines the stability of a system as a whole. The stability is rather maintained by sharing power mechanism to advance the self-empowerment process of non-center entities, which allows them to emerge as new powers. This understanding indicates the urgency to re-evaluate the current planning approach that focuses mainly on the implementation of the size-based paradigm, which is deterministic and always positions the center as a major decisive power.Keywords. center, geopolitical order, regional and urban planning, swidden tradition, the Land of Sunda.Abstrak. Penelitian ini bertujuan untuk membuka diskursus baru mengenai peran dan kedudukan pusat dalam perencanaan wilayah dan kota dengan menempatkannya sebagai metafora. Dengan memanfaatkan metode dekonstruksi metaforik, penelitian ini menelaah perubahan tatanan geopolitik dan konsep pusat di Tanah Sunda yang berbasis tradisi ladang sebagai implikasi dari masuknya ajaran Hindu dan Islam. Hasil penelitian memperlihatkan bahwa terhitung sejak sebelum kedatangan ajaran Hindu hingga masa kejayaan kekuasaan Islam di abad ke-15, tatanan geopolitik di Tanah Sunda telah mengalami transformasi, yaitu dari (1) tatanan egaliter tanpa pusat ke (2) tatanan egaliter dengan pusat yang tersembunyi dan akhirnya ke (3) tatanan jaringan-hierarkis dengan pusat yang berani tampil. Transformasi tersebut tidak sepenuhnya menghilangkan tradisi ladang, yaitu melalui pemberlakuan konsep âdalamâ dan âluarâ yang merepresentasikan prinsip kemandirian dan kebersamaan. Kedua prinsip tersebut merupakan ciri utama tatanan geopolitik di Tanah Sunda yang bersifat ekologis dan plural. Pembelajaran yang dapat ditarik dari kedua sifat itu adalah bahwa pusat tidak selalu identik dengan dominasi dan absolutisme kekuasaan. Pusat bukan satu-satunya titik yang menentukan keseimbangan suatu sistem. Keseimbangan sistem diwujudkan melalui mekanisme pembagian peran antara pusat dan non-pusat yang memungkinkan terjadinya proses penguatan diri secara spontan pada entitas di luar pusat. Pemahaman ini mengisyaratkan perlunya penilaian ulang terhadap paradigma perencanaan berbasis ukuran yang bersifat deterministik serta senantiasa memposisikan pusat sebagai kekuatan besar yang menentukan.Â Â  Â Kata kunci. pusat, perencanaan wilayah dan kota, tatanan geopolitik, Tanah Sunda, tradisi ladang.